Kategoria czasu w badaniach pedagogicznych (z koncepcją analizy transakcyjnej w tle) - Motyl , Karol (Studia Edukacyjne, 2019)
A purpose of this text is to describe how the concept of time is used in pedagogical research. An author characterizes research of educational reality in which the described category is used. Thanks to this, the potential of the concept of time was presented. The author concludes that the possibilities of this category are not used in pedagogical research and that the temporal dimension of education offers enormous exploratory possibilities. The text is completed with the characteristics of time structuring in transactional analysis as one of the ways to temporarily conceptualize interpersonal relationships in educational institutions.